Early Indicators of Academic Difficulties in Children with Neurofibromatosis Type 1 - (:unkn) unknown (My University, 2013)
Neurofibromatosis type 1 (NF1) is a genetic neurocutaneous disorder, with an estimated incidence of 1 in 3,000 persons. It is phenotypically variable disorder associated with elevated rates of intellectual disability and learning disabilities, attention problems, speech and language impairment, and executive functioning deficits. Research investigating the presentation of NF1 in preschool-age children is limited, but the data available indicate that cognitive difficulties are present and can be identified at an early age. There is also evidence from the general population that early neuropsychological deficits can be used to predict concurrent and later learning difficulties. The goal of the current study was to characterize the early learning profile of young children with NF1 and to determine which neuropsychological skills may contribute to academic difficulties. The results indicate that early learning difficulties are present and can be identified in young children with NF1. General intellectual functioning was strongly related to academic performance and accounted for many of the relations between neuropsychological and academic skills in the NF1 group. However, some specific neuropsychological skills continued to relate to foundational reading and math skills even when controlling for overall developmental level. These findings provide an indication of processing domains that may support academic skill development for future longitudinal work. Clinically, the findings suggest that cognitive screenings should be a routine part of care for young children with NF1. If appropriate interventions are implemented at an early age, academic skill development could be altered, preventing subtle learning difficulties from becoming more pronounced over time.
Keywords: Neurofibromatosis